FORMULASI SABUN CAIR PENCUCI TANGAN YANG MENGANDUNG EKSTRAK DAUN KEMANGI (Occimum basilicum L.) - Nurlina Nurlina; Faisal Attamimi; Rosvina Rosvina; M. Ilham Tomagola (As-Syifaa Jurnal Farmasi, 2013)
A study about formulation Handwash liquid soap which contain etanol extract of occimum folium (Ocimum basilicum L.). Has been conducted. This study aims to product the stable formulation of handwash liquid soap which contain etanol extract of occimum folium (Ocimum basilicum L.).This study was conducted using three variations of viscosity agent. Then do some test with storage method with organoleptic parameters, pH, foaming test, viscosity and type of flow, before and after imposed conditions.Organoleptic test result showed theres no change at II and III, test showed that is stable because still at soap pH before and after imposed condition. Statistical analysis of viscosity test showed there is difference for each formula before and after storage condition. Yield value showed difference yield value before and after strorage condition and at formula there no difference. At rheogram curve theres coincides at formula III before and after imposed condition. For foaming test , three formula is stable because theres have a good foam. The conclusion is the stable handwash liquid soap is formula III. Key words : Formulation, Handwash Liquid Soap, Occimum folium